2017
DOI: 10.1111/ijau.12107
|View full text |Cite
|
Sign up to set email alerts
|

Audit partner industry specialization and audit quality: Evidence from Spain

Abstract: We investigate the impact of the industry specialization of individual auditors on audit quality. We aim to contribute to a quickly growing line of research examining the importance of audit partners as determinants of audit quality. To provide robust results, we use several proxies of both industry specialization and audit quality. We conduct the empirical analysis with a sample of Spanish listed companies for the research period between 2005 and 2013. Our main result is the lack of a significant impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
(157 reference statements)
0
16
0
1
Order By: Relevance
“…For example, Lobo (2017) and Piot (2010) reported less or no transparency for firms audited by a Big 4 pair, suggesting that the competence and independence of a single Big 4 auditor are sufficient to ensure high audit quality. Recently, Garcia-Blandon and Argiles-Bosch (2018) investigated the impact of the industry specialization of individual auditors on audit quality. Using a sample of Spanish listed companies for the period between 2005 and 2013, they found that the industry specialization of audit partners has no effect on audit quality.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…For example, Lobo (2017) and Piot (2010) reported less or no transparency for firms audited by a Big 4 pair, suggesting that the competence and independence of a single Big 4 auditor are sufficient to ensure high audit quality. Recently, Garcia-Blandon and Argiles-Bosch (2018) investigated the impact of the industry specialization of individual auditors on audit quality. Using a sample of Spanish listed companies for the period between 2005 and 2013, they found that the industry specialization of audit partners has no effect on audit quality.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Given the upsurge regulatory interest about the mandatory publication of the APS' names, an increasingly growing number of studies have linked audit quality with a large set of APS attributes such as industry specialization (e.g. Zerni, 2012;Garcia-Blandon and Argiles-Bosch, 2018), tenure (e.g. Laurion et al, 2017;Sharma et al, 2017), workload (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2010) and T. C. Huang et al (2016) that use Chinese data for analyses and those obtained in Garcia-Blandon and Argiles-Bosch (2016) that use Spanish data. Similarly, we find that the board governance and the audit committee (as captured by IND_DIR, Meeting , and Audit_COM ) seem not having significant impact on client restatement, which is nevertheless similar to the findings of Beasley (1996) and Peasnell et al (2005) that, respectively, use financial statement fraud identified by SEC sanctions and abnormal accruals to capture the impact of board governance on financial reporting quality.…”
mentioning
confidence: 99%